Chế độ địa chấn và động đất cực đại đới đứt gãy Sông Hồng - Thủy, Nguyễn Ngọc; Hùng, Phạm Quang (Vietnam Journal of Earth Sciences, 2000)
Seismic regime and fiiarimum of earthquake's magnitude in Red River Fault zones